2013
DOI: 10.1167/iovs.13-12203
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor-β2 Induces Expression of Biologically Active Bone Morphogenetic Protein-1 in Human Trabecular Meshwork Cells

Abstract: BMP1 is expressed in the human TM. TGF-β2 induction of BMP1 may be responsible for increased processing of growth factors and ECM proteins into their mature forms, resulting in TM stiffness and resistance to ECM degradation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…We recently reported that TM cells and tissues express BMP-1 mRNA and protein and that BMP-1 protein is induced by TGF-β2. 22 Using a LOX activity assay, we also demonstrated that secreted BMP-1 from human TM cells was biologically active and increased secreted LOX enzyme activity. Significantly, we showed that glaucomatous TM cells secreted higher levels of BMP-1 and that BMP-1 secretion in glaucomatous TM cells was further induced by exogenous TGF-β2 treatment compared to normal TM cells.…”
Section: Bone Morphogenetic Protein-1 (Procollagen C-proteinase)mentioning
confidence: 74%
See 1 more Smart Citation
“…We recently reported that TM cells and tissues express BMP-1 mRNA and protein and that BMP-1 protein is induced by TGF-β2. 22 Using a LOX activity assay, we also demonstrated that secreted BMP-1 from human TM cells was biologically active and increased secreted LOX enzyme activity. Significantly, we showed that glaucomatous TM cells secreted higher levels of BMP-1 and that BMP-1 secretion in glaucomatous TM cells was further induced by exogenous TGF-β2 treatment compared to normal TM cells.…”
Section: Bone Morphogenetic Protein-1 (Procollagen C-proteinase)mentioning
confidence: 74%
“…Significantly, we showed that glaucomatous TM cells secreted higher levels of BMP-1 and that BMP-1 secretion in glaucomatous TM cells was further induced by exogenous TGF-β2 treatment compared to normal TM cells. 22 …”
Section: Bone Morphogenetic Protein-1 (Procollagen C-proteinase)mentioning
confidence: 99%
“…38 In addition, secreted protein acidic and rich in cysteine (SPARC), BMP1, and more related findings were proved responsible for ECM protein production and IOP upregulation. [39][40][41] To our knowledge, only several previous studies have taken advantage of miRNAs in regulating the biological behaviors of TM and offered a potential opportunity to identify biomarkers for diagnosis and prognosis of glaucoma. 27,42,43 MiR-24 can directly target 3 0 -UTR of the subtilisin-like proprotein convertase Furin, which could activate TGF-b1.…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β1 can induce the up-regulation of several important structural ECM proteins such as collagens and fibronectin and, in general, can modulate negatively or positively the expression of a large variety of matrix proteins, proteinases (among which BMP-1 and mTLD [39,40]), proteinase inhibitors and growth factors. Even more strikingly, TGF-β1 can drastically modify the nature of the proteins expressed by a given cell type, for example through the induction of EMT (epithelial to mesenchymal transition) [41].…”
Section: Activation Of Signaling Moleculesmentioning
confidence: 99%